Relational practices, participative organizing - Steyaert, Chris; Looy, Bart van (Advanced series in management, 2010)
"This book focuses on the concept and role of relational practices as a way to understand and study processes of organizing. Relational practices are conceived as an ongoing, everyday process resulting in more participative ways of organizing. Participative organizing works from and with the multiplicity of interactions inherent in processes of becoming; it reflects upon and experiments with how the diversity of participants and interactions can provide the potential for defining and redefining organizational realities.A" Through reflective essays and empirical research examples, this book illustrates that relational practices of everyday organizational life are strongly entangled with emotional, embodied, and aesthetic processes. The combination of these corollaries of participative organizing -- as an everyday, complex accomplishment, poised between intervention and invention, and between an affective and aesthetic ecology of belonging and becoming -- provides a new perspective on how the practice of organizing and the organizing of practice can be accomplished and managed in the years to come."